Fatty Acid Analysis Of Neatsfoot Oil From Cattle and Poultry - Krishnaraja, A.; Kulkarni, V.V.; Visha , P.; Selvaraj, P. (Journal of Meat Science, 2011)
The yield of crude neatsfoot oil from cattle and poultry was 8.77 and 0.12 % respectively. The colour of oil from cattle was yellow and that from poultry was straw green. Fatty acid analysis revealed the oleic and linoleic acid (%) as 40.95 and 50.30% for cattle and 35.25 and 2.1% for poultry, respectively.